Pengembangan Media Pembelajaran Interaktif Berbasis Visual Basic for Application (VBA) pada Microsoft PowerPoint untuk Materi Bilangan Berpangkat - Nurul Pakaya; Yamin Ismail; Perry Zakaria; Dewi Rahmawati Isa (Research in the Mathematical and Natural Sciences, 2026)
This study is a research and development study aimed at producing a learning media based on Visual Basic for Application (VBA) in Microsoft PowerPoint for the topic of exponents. The research was conducted in the first semester of the 2024/2025 academic year at MTs. Al-Khairaat Gorontalo City, involving 20 students of class VIII D as the trial participants. The development process followed the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The results indicate that the developed learning media meets the criteria of validity and practicality. Based on validation by six validators, the average validity score of the media was 3.34 and the material validity score was 3.17, both categorized as valid. Furthermore, the practicality test showed that the percentage of student responses was 87.88% and the teacher response was 100%, both categorized as very practical. Therefore, the VBA-based learning media in PowerPoint is considered feasible and appropriate for use in teaching the topic of exponents.